Hyperbaric oxygen treatment attenuates naloxone-precipitated opioid withdrawal behaviors and alters microglial activity in male and female mice - Meg T. Southard; Giuseppe Giannotti; Amit Thakar; Trinity R. Willsey; Lydia G. Bailey; Frank Salazar; Shane Hentges; Raymond M. Quock; Travis E. Brown (Scientific Reports)
Abstract Opioid use disorder poses a complex challenge marked by high relapse rates, which stem from an intricate interplay between physical dependence and psychological vulnerabilities. Previous research has demonstrated that hyperbaric oxygen treatment (HBOT), exposure to 100% oxygen under elevated pressure, reduced physical withdrawal symptoms in morphine-dependent male mice. However, remaining unknown are the effects of HBOT in female mice, its impact on the rewarding and aversive behaviors associated with morphine exposure, and the underlying mechanisms that may be driving these effects. We confirmed the beneficial effects of HBOT in reducing physical withdrawal signs in male mice and, for the first time, demonstrated that HBOT also alleviates these symptoms in female mice. HBOT had no significant effect on morphine-conditioned place preference or conditioned place aversion, suggesting that our HBOT regimen does not influence motivated behaviors. Finally, we show that HBOT treatment reduces microglial soma volume in morphine-treated male and female mice in the paraventricular thalamus, suggesting a shift towards a “resting” state after HBOT. These findings collectively suggest that HBOT may offer a promising, non-pharmacological approach to mitigating opioid withdrawal symptoms across sexes, potentially through modulation of microglia.